Mammalian fatty acid synthase: a commonly used viral host dependency factor and a putative target for host-targeted broad-spectrum antiviral therapeutic development - Paola N. Loperena González; Krithika P. Karthigeyan; Jacqueline Corry; Anurup Krishna; Ben Hackenberg; Beatriz Sierra; Jesse J. Kwiek (mBio)
ABSTRACT Viruses regulate host processes to create cellular environments favorable to viral replication. At least 27 viruses that infect humans require host fatty acid synthase (FASN)-dependent de novo fatty acid biosynthesis, including viruses from the Coronaviridae, Flaviviridae, Herpesviridae, Picornaviridae, Retroviridae, and Togaviridae families. How could FASN activity and subsequent de novo fatty acid production impact viral replication? FASN activity produces the fatty acid palmitate, which can be further metabolized into fatty acids that are used to form lipid droplets that can be used during viral assembly and budding, for beta-oxidation to generate ATP, and to create fatty acyl groups used for post-translational protein modification to change the subcellular localization of viral or host proteins. In this minireview, we outline the function of FASN, review the mechanisms linking virus replication and fatty acid biosynthesis, and consider the potential of FASN as a target for broad-spectrum antiviral drug development.